Analysis of the Acute Effects of Self-Myofascial Release and Dynamic stretching on Hamstring Flexibility in Individuals with Hamstring Tightness - Intantri, Raisyah; Wahyono, Yulianto; -, Sugiono - (UI Scholars Hub, 2025)
Background: Sedentary behavior among college students leads to decreased physical activity, which negatively affects physical fitness, especially by reducing muscle flexibility. Self-Myofascial Release (SMFR) and Dynamic stretching (DS) are exercise interventions that have the potential to improve muscle flexibility. Objective : This study aimed to compare the acute effects of Self-Myofascial Release and Dynamic stretching on hamstring flexibility in students with hamstring tightness. Methods: This study employed a two-group pre-test and post-test design conducted in May at Poltekkes Surakarta. Participants were selected using simple random sampling and divided into two groups: SMFR (n=19) and DS (n=19). Each group received a single intervention. Hamstring flexibility was measured using the Active Knee Extension Test with a goniometer before and after treatment. Results : Statistical analysis using the dependent t-test showed significant improvement in both groups (Group I: p = 0.000; Group II: p = 0.000, p= Conclusion : Both Self-Myofascial Release and Dynamic stretching produce acute effects in improving hamstring flexibility. However, Dynamic stretching is more effective than Self-Myofascial Release in increasing hamstring flexibility among students with hamstring tightness.